Reducing Student Food Waste on Campus - Hamer, Anna G.; Salzer, Allyson R.; Lagorio, Carla H. (My University, 2017)
The current study focused on the primary cafeteria on the campus of the University of Wisconsin‐Eau Claire. Recent environmental and social justice movements have emphasized the importance of reducing food waste, due to the energy required to produce and transport food, as well as the millions of individuals living in food‐ deprived conditions.
Color poster with text, graphs, and images.
Keywords: Composting; Cafeterias; Food waste; Posters